The Power to Coerce Countering Adversaries Without Going to War - Gompert, David C. (RAND Corporation, 2016)
Mounting costs, risks, and public misgivings of waging war are raising the importance of U.S. power to coerce (P2C). The best P2C options are financial sanctions, support for nonviolent political opposition to hostile regimes, and offensive cyber operations. The state against which coercion is most difficult and risky is China, which also happens to pose the strongest challenge to U.S. military options in a vital region.